Trend in Land Use/Cover Changes in Stubbs Creek Forest, Akwa Ibom State, Nigeria - Jacob; I. U., Nelson; K. S., Okoh; Tom, A. A. (International Journal For Research In Business, Management And Accounting, 2015)
This study examined the land cover changes in Stubbs Creek, Nigeria using a combination of satellite remote sensing and ground data with the aim of determining the spatial extent and trend of changes of forest landscape in the area using three epochs of satellite imagery (1986, 2000 and 2014) The results indicated that the spatial extent and trend of forest landscape changes within the 28 years period under study (1986 – 2014) showed a decrease of -292.73ha (0.66%) of water bodies with an annual trend of 10.45ha, 11,519.29ha (25.84%) for primary forest with annual trend of 411.40ha and -10,478 (23.50%) hectares for secondary forest with annual trend of 374.21ha, while cultivated lands and Built-up/Bare lands increased by 18,211.79ha (40.86%) and 4,078.23 (9.11%) with an annual trend of 650.48ha and 145.65ha respectively. All land cover changes followed a positive coefficient of correlation. An urgent review of the management of the forest structure in the state, especially around the coastal region is recommended to curtain flooding and erosion.